Millennial hydrological variability in the continental northern Neotropics during Marine Isotope Stages (MISs) 3–2 (59–15 cal ka BP) inferred from sediments of Lake Petén Itzá, Guatemala - Martínez-Abarca, Rodrigo; Abstein, Michelle; Schenk, Frederik; Hodell, David; Hoelzmann, Philipp; Brenner, Mark; Kutterolf, Steffen; Cohuo, Sergio; Macario-González, Laura; Stockhecke, Mona; Curtis, Jason; Anselmetti, Flavio S.; et al. (Climate of the Past, 2023)
Lake Petén Itzá (Guatemala) possesses one of the longest lacustrine sediment records in the northern Neotropics, which enabled study of paleoclimate variability in the region during the last 400000 years. We used geochemical (Ti, Ca=(TiCFe) and Mn=Fe) and mineralogical (carbonates, gypsum, quartz, clay) data from sediment core PI-2 to infer past changes in runoff, lake evaporation, organic matter sources and redox conditions in the water column, caused by hydrological changes in the northern Neotropics during Marine Isotope Stages (MISs) 3–2. From 59 to 39 cal ka BP climate conditions were relatively wet, and the lake was marked by higher primary productivity and anoxic bottom waters. This wet environment was interrupted for two periods of possible low water level at 52 and 46 cal ka BP, when our data suggest higher evaporation, high terrestrial organic matter input and persistent oxic conditions. Between 39 and 23 cal ka BP, evaporation and input of terrestrial organic matter increased considerably, lake level declined, and lake bottom waters generally became oxic. These conditions reversed during the Last Glacial Maximum (23.5–18.0 cal ka BP), when runoff and lake productivity increased, and rising lake level caused bottom waters to again become anoxic. Comparison of our hydrologic proxy data with sea surface temperature anomalies between the eastern Pacific and the Caribbean suggests that changes in the intensity of the Caribbean Low-Level Jet (CLLJ) may have influenced long-term changes in runoff during MISs 3–2. Higher intensity of the CLLJ during the onset of MIS 3 and the LGM might have led to greater runoff into the lake, whereas the MIS 3–2 transition experienced a weaker CLLJ and consequently less runoff. A refined, high-resolution age–depth model for the PI-2 sediment core enabled us to identify millennial-scale Greenland interstadials (GIs) 14–2, Greenland stadials (GSs) 14–2 and Heinrich stadials (HSs) 5–1. In general, HSs and GSs were characterized by drier conditions. In contrast to GSs and HSs, ...